Pelatihan Pemanfaatan Hyperlink pada Presentasi Guru SMA Negeri 1 Kampar - Mustika, Tria Putri; Elmustian; Dudung Burhanudin; Elvrin Septyanti; Oki Rasdana; Firajul Afkar Asra (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2023)
Presentations become an important weapon for teachers in the classroom. This is what makes the teacher the most important person in the class when learning is done. It is the teacher's presentation that makes it easy for students to understand until later they really understand the material that must be achieved by each student. Based on this, the author plans training on the use of Hyperlink for teachers in schools. The hope is that through this training, teachers will have easy and inexpensive technological competencies. In accordance with what he understands himself, according to the conditions in his own class or school so that it will be more adaptable, effective, and efficient because the teacher utilizes simple technology